Genetic architecture of photosynthesis in Sorghum bicolor under non-stress and cold stress conditions - Ortiz, Diego (2017)
Sorghum (Sorghum bicolor L. Moench) is a C4 species sensitive to the cold spring conditions that occur at northern latitudes, especially when coupled with excessive light, and that greatly affect the photosynthetic rate. The objective of this study was to discover genes/genomic regions that control the capacity to cope with excessive energy under low temperature conditions during the vegetative growth period. A genome-wide association study (GWAS) was conducted for seven photosynthetic gas exchange and chlorophyll fluorescence traits under three consecutive temperature treatments: control (28 °C/24 °C), cold (15 °C/15 °C), and recovery (28 °C/24 °C). Cold stress significantly reduced the rate of photosynthetic CO2 uptake of sorghum plants, and a total of 143 unique genomic regions were discovered associated with at least one trait in a particular treatment or with derived variables. Ten regions on chromosomes 3, 4, 6, 7, and 8 that harbor multiple significant markers in linkage disequilibrium (LD) were consistently identified in gas exchange and chlorophyll fluorescence traits. Several candidate genes within those intervals have predicted functions related to carotenoids, phytohormones, thioredoxin, components of PSI, and antioxidants. These regions represent the most promising results for future validation and with potential application for the improvement of crop productivity under cold stress.